Chemometrics analysis combined with GC-MS and NMR spectroscopy analysis of fatty acids as a means of discriminating butterfat adulteration - Ahmad Fadzillah, Nurrulhidayah; Rohman, Abdul; Ismail, Amin; Abdul Manaf, Yanty Noorzianna; Rosman, Arieff Salleh; Khatib, Alfi; Mohd Hassan, Norazian; Othman, Rashidi (Science Education Technology (SET) Publisher, 2019)
The adulteration of butter has become a major problem in food industries. Butter has a similar characteristic to lard which makes lard a desirable adulterant in butter due to economic advantages. Therefore, the method of detection to analyse the adulteration practice must be developed. This study used NMR spectroscopy in combination with chemometrics for the authentication of butter from lard. The presence of lard as an adulterant in butter has been analysed using Gas Chromatography-Mass Spectrometry (GC-MS) and Nuclear Magnetic Resonance (NMR) spectroscopy with the aid of chemometric of Principal Component Analysis (PCA) and Discriminant Analysis (DA). PC1 described 82% of the variation while PC2 accounted for 15% of the variation resulted in a model that described 80% of the total variance in the data. With 82% of the peak variation along the first PC, it was clear that all seventeen samples of butter in the market and pure lard sample were formed according to their own group and showed two well-defined and well-separated group. DA model classified 100% of all samples accurately according to its group (butter and butter adulterated with animal fats), meaning that no samples were misclassified into the wrong group. Lard was successfully determined at 2.63 ppm. In this study, NMR and PCA analysis have successfully discriminated between the market sample and lard and the results established that there is no lard being adulterated in all commercial butter samples. This could be a potential identification approach to determine if the product has been deceived in the market.